Psychoeducation and Self Esteem Improvement Among Junior High Bullying Victims: Pendidikan Psikologis dan Peningkatan Harga Diri pada Korban Perundungan di Sekolah Menengah Pertama - Moch Bachrul Sidik; Nurfi Laili (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Bullying remains a persistent school-based social problem affecting students’ psychological well-being and academic adjustment. Specific Background: Low self-esteem increases vulnerability among bullying victims, while psychoeducation has been proposed as a preventive and rehabilitative strategy. Knowledge Gap: However, empirical evidence on structured psychoeducational programs in Indonesian junior high schools is still limited. Aims: This study examined psychoeducation in strengthening self-esteem among bullying victims at SMP Negeri 2 Wonoayu. Results: Using a quasi-experimental one-group pretest–posttest design involving 15 students, significant improvement was found between pretest (26.27) and posttest (34.73) scores (Sig. 0.000). Students demonstrated better emotional regulation, self-acceptance, and resistance to peer pressure after the intervention. Novelty: This research provides school-based evidence of psychoeducation as a cognitive–educational intervention targeting self-esteem recovery among adolescent bullying victims. Implications: The findings support psychoeducation as a preventive school strategy to foster supportive learning environments and promote students’ psychosocial resilience. Keywords: Psychoeducation, Bullying, Self Esteem, Junior High School, Student Mental Health Key Findings Highlights: Significant score improvement observed after structured intervention. Participants showed positive cognitive and emotional shifts. School-based programs support healthier peer environments.